Tuning the Reactivity of Ultrathin Oxides: NO Adsorption on Monolayer FeO(111). (27th June 2016) - Merte, Lindsay R.; Heard, Christopher J.; Zhang, Feng; Choi, Juhee; Shipilin, Mikhail; Gustafson, Johan; Weaver, Jason F.; Grönbeck, Henrik; Lundgren, Edvin
Abstract: Ultrathin metal oxides exhibit unique chemical properties and show promise for applications in heterogeneous catalysis. Monolayer FeO films supported on metal surfaces show large differences in reactivity depending on the metal substrate, potentially enabling tuning of the catalytic properties of these materials. Nitric oxide (NO) adsorption is facile on silver‐supported FeO, whereas a similar film grown on platinum is inert to NO under similar conditions. Ab initio calculations link this substrate‐dependent behavior to steric hindrance caused by substrate‐induced rumpling of the FeO surface, which is stronger for the platinum‐supported film. Calculations show that the size of the activation barrier to adsorption caused by the rumpling is dictated by the strength of the metal–oxide interaction, offering a straightforward method for tailoring the adsorption properties of ultrathin films.